REUSE OF DOMESTIC WASTEWATER FOR IRRIGATION: CONCEPTUAL AND BASIC DESIGN ELEMENTS - Mohamed Ali, Abdul-Fattah (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
In Iraq, water shortages and drought, especially during the hot summer months, necessitates that municipal authorities adopt water reuse projects like reusing treated domestic wastewater for crop irrigation. This work gives the conceptual and basic design elements for the necessary steps of filtration, UV irradiation and chlorination to make such a wastewater fit for agricultural use. A typical rural community of 50,000 people is considered as an example case for which functionality and relative simplicity of the proposed designs are prime factors. The objectives are 1) to show what is required and 2) that the presented information may be utilized to embark on the following phases of detailed design and execution of such projects.